Factors Influencing the Presence of Papilla between Adjacent Implants and between a Tooth and an Implant - Camila Agra Souza; Roberto Carlos Mourão Pinho; Rafael Amorim Cavalcanti de Siqueira; Alexia Luíse Freitas Santos de Andrade; Bruna de Carvalho Farias Vajgel; Joaquim Celestino da Silva Neto; Renata Cimões (University of Zagreb. School of Dental Medicine, 2019)
Aim: The aim this study was to evaluate the factors that influence the presence or absence of the interproximal papilla between implants adjacent to the teeth or other implants, through clinical and radiographic evaluation. Material and Methods: The non-probabilistic sample comprised 44 patients of both genders aged between 21 and 68 years, rehabilitated with 114 osseointegrated implants. Through a retrospective clinical study, the patients were divided according to the presence or absence of the interproximal papilla: Group 1 - Absence of Papilla, Group 2 - Partial Presence of Papilla and Group 3 - Total Presence of Papilla. The success of the implants, the periodontal biotype, and the vertical and horizontal distances of the interproximal regions included in the study were evaluated. Results: Of the 114 implants, 46.5% were considered unsuccessful, and bleeding was resent in 29.8%. The periodontal biotype presented as thin and scalloped was found in 85.1% of the regions. The evaluation of the groups according to the confirmation of the interproximal space showed a statistically significant difference (p = 0.007), with 61.9% of the wide and long interproximal spaces classified as Group 1, while 31% of the narrow and short interproximal spaces were classified as Group 3. Conclusion: It was concluded that the morphology of the interproximal space was the factor that was most strongly associated with the presence or absence of the interproximal papilla.